PENERAPAN METODE EARLIEST DUE DATE DAN APPOINTMENT SCHEDULING PADA SISTEM INFORMASI IMUNISASI BALITA DI PUSKESMAS SIMUNDOL - Rani Ritonga; Raissa Amanda Putri (LPPM Universitas Abdurrab, 2026)
Childhood immunization services play an important role in improving children's health status. However, the recording and delivery of immunization schedule information at Simundol Public Health Center still faces challenges, such as delayed information, dependence on the maternal and child health handbook (KIA), and the absence of a structured immunization prioritization system. This study aims to design and develop a web-based child immunization information system by implementing the Earliest Due Date (EDD) and Appointment Scheduling methods, using a Research and Development (R&D) approach with the 4D model and the Waterfall development method. The resulting system involves two actors, namely admin and parents, with eight main modules covering child data management, automatic immunization prioritization based on due date (EDD), visit scheduling (appointment scheduling), immunization history, and reporting. The results indicate that the EDD method is able to sort immunization priorities automatically and in real time based on the nearest due date, while appointment scheduling helps organize visit schedules in a structured manner to reduce queue buildup. The system also makes it easier for parents to obtain digital information on their children's immunization schedules and history, replacing the maternal and child health handbook. Therefore, the implementation of EDD and Appointment Scheduling in the child immunization information system can improve data management efficiency and the timeliness of immunization services at Simundol Public Health Center.